The Risk of Hypothecary Credit Indexed to Swiss Franc - Zemke Jerzy (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
The idea of crediting and credit repayment is based on an assumption that each payment of the principal reduces the debt balance. This tendency is not followed in case of the hypothecary credit allowed and paid out in PLN and indexed to Swiss franc. Here, the balance of principal repaid in PLN is a function of currency exchange rate fluctuations. The situation denies then the idea of credit, according to which "you pay back as much as borrowed”. The cost of credit, calculated as a total of the LIBOR - credit in CHF (WIBOR - credit in PLN) rateand the bank's margin specified in the contract. The purpose of the paper is to prove that a banking product like this does not meet the standards of crediting, the principal balance being dependent on the unforeseeable direction of changes. The purpose of the paper is to design a model of risk of the hypothecary credit indexed to Swiss franc, to enable the measurement of the loan payment risk. The model design methodology assumes control variables of the risk monitoring process to be included in the model structure. The estimated loan payment risk measures have revealed an upturn in the loan payment risk related to higher PLN/CHF rates and the resultant higher cost of credit accompanied by the loan principal growth. The risk dynamics estimations for the years 2006 – 2012 support the research thesis – the banking product analysed does not show the characteristics of a loan. Under growing PLN/CHF rates, the loan principal indexation translates into the debt balance escalation.
Keywords: G21; 330; hypothecary credit; credit indexed to Swiss franc; credit risk of indexed to Swiss franc; risk measurement